Answer:
![y\leq -6](https://img.qammunity.org/2022/formulas/mathematics/college/u9k8gym9yur1hdgb26t7ldghxjw2s38gmh.png)
Explanation:
![(1)/(2)y \leq -3](https://img.qammunity.org/2022/formulas/mathematics/college/viain0vyn7q038nb1glwopudlfl7mmuumk.png)
Our inequality requires first to solve for y.
To solve for a variable, we must isolate it.
In this case, first, we can multiple by the inverse of the fraction which is 2.
![(1)/(2)y\leq -3\\](https://img.qammunity.org/2022/formulas/mathematics/college/4dsre1v8qsxzdwtvuvh9nlhgadx71vw531.png)
![2((1)/(2)y)\leq -3(2) \\](https://img.qammunity.org/2022/formulas/mathematics/college/q178uz8awov6otgtraxu4e0pwxgz2msg4p.png)
1*y=y and -3*2=-6
So our inequality stands like this -
![y\leq -6](https://img.qammunity.org/2022/formulas/mathematics/college/u9k8gym9yur1hdgb26t7ldghxjw2s38gmh.png)
When graphing, it must look like this: